Optical and ultrastructural study of the pollen grain development in hermaphrodite papaya tree (Carica papaya L.) - Santos,Lídia Márcia Silva (2008)
The objective of this study was to describe the pollen grain development in hermaphrodite papaya tree. The flower buds were collected at different stages of the development and the anthers were treated chemically for observation under optical and electronic transmission microscopes. The pollen grain development followed the normal pattern described for the Angiosperms. The pollen grain development was described from meiocyte to the mature pollen grain. In the microsporogenesis, the microspore mother cells or the meiocytes underwent meiosis giving rise to the tetrads that were enclosed by the calose. Later, the tetrads were released by the dissolution of the calose by calase activity and microspores underwent mitosis. Microgametogenesis was characterized by asymmetrical mitotic division of each microspore giving rise to bi-nucleate pollen grains. The structures similar to the plastids were found in the cytoplasm and close to the nucleus of the generative cell. Gradual degeneration was observed in the tapetum during the male gamete development.